COLOGICAL IMPERIALISM AND SUBALTERN RESISTANCE: AN ECOCRITICAL ANALYSIS OF THE SELECTED FICTION OF AMITAV GHOSH - Singh, Embrose; Jaiswal, Monika (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The irreversible effect of human activity on the global ecosystem is shared in literature in the epoch of the Anthropocene as a critical imaginative archive. The paper is a critical analysis of Amitav Ghosh fiction of the selected works: The Glass Palace (2000), The Hungry Tide (2004) and the Ibis Trilogy (2008-2015) using the theoretical frameworks of Ecocriticism, Social Ecology and Ecofeminism. Using the theories of hierarchical domination by Murray Bookchin and the ecofeminist critique of capitalist patriarchy by Vandana Shiva, this paper will explore how Ghosh traces the history of environmental degradation since the colonial period to the contemporary climate crisis. The article suggests that the stories of Ghosh reveal an Ecological Imperialism showing how exploitation of nature world is bound to the systematic oppression of the marginalized human beings. By analyzing in detail, the ecocide of colonialism in Burmese teak forests, state-sponsored eco-fascism in the Sundarbans, and botanical imperialism in the Gangetic plains through opium monoculture, this paper concludes that Ghosh needs a paradigm shift in his fiction. It questions the anthropocentric avarice and promotes bioregional concord, saying that the environment cannot be preserved unless the social hierarchies that subjugate the subaltern are overthrown.